Theories for sustainable futures - Holling, C S (Himalayan Journal of Sciences, 2006)
According to Holling, sustainable development and management of natural resources is failing because it spans the domains of economy, ecology, and social science. Policies and programs have typically been driven by interests representative of one of these fields, each of which has its own established theoretical structure. What is required is a theoretical edifice that integrates all three. For five years, the Resilience Project has been assembling just such a theory, one that not only embraces all relevant fields, but also is simple enough to be generally understood and complex enough to handle the guide the formulation of sustainable development policy.*Reprinted with permission from Conservation Ecology (now renamed as Ecology and Society), Vol 4, Issue 2. Copyright © 2000 by The Resilience Alliance.* Subtitle and Summary not from Conservation Ecology; added with the permission by the Himalayan Journal of SciencesHimalayan Journal of Sciences 2(3): 12-14, 2004The full text is of this article is available at the Conservation Ecology website